Molecular characterization of Alternaria alternata population isolated from Upper Egyptian tomato fruits. Issue 10 (20th July 2018) - Gherbawy, Youssuf; Hussein, Mohamed A.; Runge, Fabian; Spring, Otmar
Abstract: Alternaria alternata is the most common fungal pathogen of tomatoes in Upper Egypt. Morphological identification of this fungus is challenging; therefore, this study searched for new classification tools based on molecular techniques. Using a dilution plating method, 67 strains of A. alternata were isolated from 34 samples of rotten tomato fruits representing the Giza 80 and Edkawy cultivars. The collected strains were identified using the amplification products of the internal transcribed spacer (ITS) region, glyceraldehyde 3‐phosphate dehydrogenase ( Gpd ) and Alt a 1, which is a gene involved in the production of most of the allergens produced by A. alternata . The screening revealed that A. alternata constituted more than half of the total fungi recovered from rotten tomatoes in this study. According to the phylogenetic analysis using these three loci, the collected strains clustered in accordance with the host cultivar type from which they had been isolated. Specific gene random primer polymerase chain reaction (SGRP‐PCR) techniques indicated that the A. alternata population in the tested region has a high genetic diversity. The pathogenicity test showed that most of the A. alternata isolates (67.2%) were highly pathogenic, and no correlation was found between the phylogenetic analysis and pathogenicity. In addition, the influence of the fungicide Disan 80% on the collected strains showed significant differences that were attributed to the source of isolation.